Demographic and cultural correlates of traditional eating among Alaska Native adults at risk for cardiovascular disease. - Mark A Sanders; Marily Oppezzo; Jordan Skan; Neal L Benowitz; Matthew Schnellbaecher; Judith J Prochaska (PLoS ONE, 2022)
This cross-sectional study assessed how traditional eating relates to cultural and community factors. Alaska Native adults from the Norton Sound region were recruited and surveyed between 2015-2018 for a randomized clinical trial of multiple risk behavior change interventions for cardiovascular disease prevention. Participants (n = 291) were 49% female with a mean age of 47 years (SD = 14). A 34-item food frequency questionnaire assessed consumption of foods traditional and nontraditional to the regional Alaska Native diet. A novel measure, termed the "traditional foods index", was computed as weekly servings of culturally traditional food consumption divided by total foods reported. Overall, the sample's traditional foods index averaged 21%±16%, with higher values reported by participants assessed in summer (23%±17%) than winter (19%±15%, p<0.05); by women (22%±16%) than men (19%±16%, p < .05); and by residents of smaller communities (22%±17%) than the comparatively larger community of Nome (17%±14%, p<0.05). The traditional foods index was correlated with age (r = .26, p < .01), as well as the cultural variables of community connectedness (r = .19, p < .01), community standing (r = .15, p < .01), and traditional language comprehension (r = .19, p < .01). In a multivariate regression model, age, community connectedness, and community standing remained significantly associated with traditional diet. These findings may inform the design and evaluation of community-based, culturally-relevant dietary initiatives for heart health.